A comprehensive review on graphene nanoparticles : Preparation, properties, and applications - Yusaf, Talal; Mahamude, Abu Shadate Faisal; Farhana, Kaniz; Wan Sharuzi, Wan Harun; Kadirgama, Kumaran; Ramasamy, Devarajan; Mohd Kamal, Kamarulzaman; Subramonian, Sivarao; Hall, Steve; Dhahad, Hayder Abed (MDPI, 2022)
Graphene, with its amazing prospects and nonpareil aspects, has enticed scientists and researchers all over the globe in a significant fashion. Graphene, the super material, endlessly demonstrates some of the substantial, as well as desired, mechanical, thermal, optical, and chemical characteristics which are just about to bring about an unprecedented transformation in the science and technology field. Being derived from graphite, graphene is made of one-atom-thick, two-dimensional carbon atoms arranged in a honeycomb lattice. This Nobel-prize-winning phenomenon includes properties that may result in a new dawn of technology. Graphene, the European Union’s (EU) largest pledged project, has been extensively researched since its discovery. Several stable procedures have been developed to produce graphene nanoparticles in laboratories worldwide. Consequently, miscellaneous applications and futuristic approaches in artificial intelligence (AI)-based technology, biomedical and nanomedicine, defence and tactics, desalination, and sports are ruling over the next generation’s fast-paced world and are making the existing market competitive and transformative. This review sheds light upon the ideology of the preparation and versatile application of graphene and foretells the upcoming advancements of graphene nanoparticles with the challenges rearing ahead. The study also considers graphene nanoparticles’ diverse fields and portends their sustainability with the possibility of their acceptance in the commercial market as well as in common usage.